Governmental Competition in Road Charging and Capacity Choice - Barry Ubbels; Erik Verhoef (Tinbergen Institute, 2006)
In this study we have analysed policy interactions between an urban and a regional government which have different objectives (welfare of its own citizens) and two policy instruments (toll and capacity) available. Using a simulation model, we investigated the welfare consequences of the various regimes that result when both governments compete, and take sequential decisions on prices and capacities. We find that competition between governments may not be very beneficial to overall welfare in society compared with one central government. It appears that the tendency of tax exporting is very strong in this setting where commuters have to pay road tolls set by the city government. The main issue is not which exact type of game is played between the two actors, but much more whether there is cooperation (leading to first-best) or competition between governments, where of secondary importance is the question who is leading in the price stage (if there is a leader). Sensitivity analysis suggests that the performance for most game situations improves when demand becomes more elastic. When the price of road investment changes, the performance relative to the optimal situation remains more or less equal for all cases.
Keywords: R4; 330; traffic congestion; road pricing; road capacity; tax competition